EDUCATION IN LIQUID SOCIETY: CHALLENGES IN TEACHING PRACTICE - da Silva Cabral, Ayrton; de Medeiros Oliveira, Antuzia; Gregório Antunes de Medeiros , Ismaelita; da Glória Gomes Silva, Maria; do Socorro Fernandes de Carvalho, Maria; Linhares de Medeiros Melo, Marina; Silas Moura, Sid (Revista Gênero e Interdisciplinaridade, 2022)
This article analyzes, from the perspective of the great Polish sociologist and philosopher, Zigmunt Bauman, Education in contemporary Society, which features characteristics of a liquid society. In order to address the challenges faced by teachers and how such liquidity influences the school environment, the theme of education in liquid society was chosen because it manifests itself as a current and innovative theme for contemporary reflection on teaching practice. Methodologically based on a qualitative and interpretive research approach, the study focused the analysis on reflections on studies of the aforementioned theorist, and on socio-emotional macrocompetencies.